Carolina Covarrubias Photograph at COVID-19 Testing Site - Covarrubias, Carolina::::::::: (2020)
The contributor writes, "Currently, I work for the City of Los Angeles. My normal duties are as a graphic designer but when the pandemic began, the Mayor reassigned all city employees to become Disaster Service Workers (DSW). The photograph shows myself and co-workers after a long day working a COVID-19 testing site. We are standing in front of the sign that directs the public to enter the site. Over 1,600 people visited that day." Pictured, left to right: Musa Khan, Carolina Covarrubias, Desiree Khan, Alex Gomez, and Edgar (unknown last name).